STRATEGI KETAHANAN SOSIAL MASYARAKAT PERKOTAAN (STUDI KASUS : KELURAHAN PETAMBURAN) - Redidzia Hernandi; Kurniawaty Iskandar (Media Bina Ilmiah, 2023)
This study examines the strategy of community social resilience in the Petamburan Village. The diversity of community backgrounds in the Petamburan Village makes the social dynamics of the Petamburan Village in the spotlight, one of which is the conflict that occurs between communities which hinders the achievement of community social resilience. This research is qualitative research with a descriptive methods. Methods of data collection using interviews conducted on three informants, observation, and documentation. This research uses the concept of social resilience according to Webersik and Collins conflict theory. Webersik explained that community social resilience can be realized with two approaches, namely the role of the government and the role of the community itself. Meanwhile, Collins' conflict theory explains that conflicts that occur in society are caused by differences in interests. The results of the study found that the causes of conflict in Petamburan Village were caused by mutual ridicule and differences of opinion between residents. The Petamburan Sub-District Government took repressive steps by issuing statements for residents who were in conflict and were fostered by the RT and RW and if it was found that these residents were having conflicts again, they would be handed over to law enforcement officials. Meanwhile, the community chose to activate youth groups at the RW and Kelurahan levels to take an inter-citizen approach with activity programs that emphasize togetherness among the community and are beneficial to the surrounding environment to reduce conflict. This is in line with the concept of community social security, namely the role of the government and the community in reducing the conflict to achieve community social resilience in Petamburan Village. In addition, the research results are also in line with the conflict theory according to Collins that conflicts that occur in the Petamburan sub-district are often based on differences of opinion or interests.